Thermal requirements, development and number of generations of Duponchelia fovealis (Zeller) (Lepidoptera: Crambidae) - Paes, Joao P. P. (2018)
In this study, the effect of temperature on the growth of the European pepper moth, Duponchelia fovealis (Zeller). was assessed at five constant temperatures (18, 21, 24, 27 and 30 degrees C). The European pepper moth was observed to complete its developmental stages (from egg to adult) at all the temperatures evaluated. From the results, it was evident that temperature affected the rate and development time of all the growth stages, to a significant degree. The length in time of the embryonic, larval, pupal and total (egg-adult) stages was observed to drop as the temperature rose from 18 to 24 degrees C, but remained constant between 27 and 30 degrees C. The developmental time in the pre-pupal stage dropped between 18 and 30 degrees C. The European pepper moth takes 454 degree-days to complete development at 11.7 degrees C temperature threshold. The D. fovealis survival was thus inversely proportional to temperature over range of 18 to 30 degrees C. On assessing the number of annual generations for the five largest strawberry-producing municipalities in Espirito Santo State, an average of 5.5 generations per year was estimated. This is a first report of temperature on D. fovealis development.